Incidence and damage of the ambrosia beetle on cocoa plants in East Luwu District, South Sulawesi, Indonesia - NURIADI NURIADI; SYLVIA SJAM; AHDIN GASSA; VIEN SARTIKA DEWI (Society for Indonesian Biodiversity, 2023)
Abstract. Nuriadi, Sjam S, Gassa A, Dewi VS. 2023. Incidence and damage of the ambrosia beetle on cocoa plants in East Luwu District, South Sulawesi, Indonesia. Biodiversitas 24: 3592-3600. The attack of ambrosia beetle on cocoa plants (Theobroma cacao L.) in East Luwu District, South Sulawesi Province, was first reported in 2020 at the Wotu sub-district. However, there was no information on its intensity and the number of affected sub-districts. A survey and data collection were conducted from January to July 2021 by selecting a 1 hectare area from 7 out of the 11 affected sub-districts identified in the preliminary study. The parameters observed were attack intensity, the number of galleries in stems and branches, and the number of trapped ambrosia beetle. The results showed that the attack of the ambrosia beetle on cocoa plants in the 7 sub-districts ranged from moderate to severe intensity, causing damage to mature plants and seedlings. It was observed that the number of galleries was higher on stems than on branches. The intensity of attacks on cocoa plants aged 23-27 years is higher than the cocoa aged 8-15 years. Additionally, the obtained species of ambrosia beetle are Xylosandrus sp.1 (Coleoptera: Curculionidae), Xylosandrus sp.2 (Coleoptera: Curculionidae), Xyleborus sp. (Coleoptera: Scolytidae) and Hypothenemus sp. (Coleoptera: Scolytidae). The results are expected to provide important information about the invasion of the ambrosia beetle and the prevention steps of its spread on cocoa plantations in South Sulawesi.